Formulasi Kebijakan Penataan Ruang Berbasis Konservasi untuk Penguatan Kabupaten Pariwisata - Budiman, Haris; Akhmaddhian, Suwari; Yuhandra, Erga (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2023)
This study discusses the formulation of regional policies in the field of conservation-based spatial planning to strengthen tourism districts. The purpose of this study is to identify and analyze the factors that influence spatial planning policies in areas that have agricultural and tourism contours. This research uses a descriptive-analytical method with a qualitative approach. The results of this study indicate that there are several factors that influence conservation and tourism-based spatial planning policies in the regions, including national policies, regional policies, community needs, and regional tourism potential. Based on the results of this analysis, the researcher recommends that tourism-based spatial planning policies in the regions should be prepared by considering these factors and involving various related parties, such as the government, community, and tourism actors. According to this article, a team or working group should be established with the express responsibility of creating, overseeing, and assessing a conservation and tourism-based spatial planning policy. Furthermore, depending on regional features, this paper proposes the creation of regional spatial planning policies by combining regional RTRW and RDTR laws into a unified policy package.